Analisis Usability Sistem Komputerisasi Haji Terpadu Palembang Menggunakan Metode System Usability Scale (SUS) - Abdurrahman Abdurrahman; Maria Ulfa (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
The Palembang Integrated Hajj Computerized System which is currently used as an information system for Hajj and Umrah pilgrims, because the entire data processing process for the purpose of making Hajj documents such as passports, departure and return flights, banking and biodata of prospective pilgrims refers to the integrated computer system. Both internally and externally there has never been an evaluation, either at the time of design, manufacture or implementation. This research was conducted with the title